INVESTIGATION OF MORAL SENSITIVITY IN NURSES - Esmailzadeh, Samineh; Nurluöz, Özdem; Çakırcalı, Emine (Revista Gênero e Interdisciplinaridade, 2021)
Nurses should have an advanced moral sensitivity, which is defined as the ability to distinguish ethical problem, in order to make the right decision regarding the identification and analysis of ethical problems.Each nurse may have different perspective on ethical problems and solution approach respectively. Moral sensitivity level in nurses is a major factor in such variation. Hence, the analysis on moral sensitivity among nurses and identification of different variables affecting their moral sensitivity are crucial. This study aims to measure the moral and ethical sensitivity of hospital nurses towards the patients and other staff. The sample of this study, which was planned as descriptive and cross-sectional, is the voluntary nurses from two training hospitals (n=600). Introductory information form and Moral Sensitivity Scale were both used in data collection. The research data was analysed with Statistical Package for Social Sciences (SPSS) 24.0. Frequency analysis was utilised for the distribution of socio-demographic characteristics; the comparison of data set with normal distribution was analysed with Kolmogorov-Smirnov test and Mann-Whitney U test and Kruskal-Wallis H test – non-parametric hypothesis tests were conducted as data found not compatible with normal distribution. In consideration with results, majority of nurses encounter with ethical problems at their departments. While 50.86% of nurses overcome such problems, around 20% of them are not able to solve their problems accordingly. Conclusion: The findings reflected that the moral sensitivity levels among nurses positively differ with their professional seniority and way of work whereas some factors negatively affect the moral sensitivity levels.